The Antiarrhythmic Drug, Dronedarone, Demonstrates Cytotoxic Effects in Breast Cancer Independent of Thyroid Hormone Receptor Alpha 1 (THRα1) Antagonism. Issue 1 (December 2018) - Elliott, Mitchell; Jerzak, Katarzyna; Cockburn, Jessica; Safikhani, Zhaleh; Gwynne, William; Hassell, John; Bane, Anita; Silvester, Jennifer; Thu, Kelsie; Haibe-Kains, Benjamin; Mak, Tak; Cescon, David
Abstract Previous research has suggested that thyroid hormone receptor alpha 1 (THRα1), a hormone responsive splice variant, may play a role in breast cancer progression. Whether THRα1 can be exploited for anti-cancer therapy is unknown. The antiproliferative and antitumor effects of dronedarone, an FDA-approved anti-arrhythmic drug which has been shown to antagonize THRα1, was evaluated in breast cancer cell linesin vitro andin vivo . The THRα1 splice variant and the entire receptor, THRα, were also independently targeted using siRNA to determine the effect of target knockdownin vitro . In our study, dronedarone demonstrates cytotoxic effectsin vitro andin vivo in breast cancer cell lines at doses and concentrations that may be clinically relevant. However, knockdown of either THRα1 or THRα did not cause substantial anti-proliferative or cytotoxic effectsin vitro, nor did it alter the sensitivity to dronedarone. Thus, we conclude that dronedarone's cytotoxic effect in breast cancer cell lines are independent of THRα or THRα1 antagonism. Further, the depletion of THRα or THRα1 does not affect cell viability or proliferation. Characterizing the mechanism of dronedarone's anti-tumor action may facilitate drug repurposing or the development of new anti-cancer agents.